Effect of Investment on Employment in the Formal Small Industries In the District/City of South Sumatra Province, Indonesia - Yuliana, Saadah; Robiani, Bernadette; Mukhlis, Mukhlis (International Journal of Economics and Financial Issues, 2018)
This study aimed to analyze the effect of the investment on employment in the formal small industries in the district/ city of South Sumatera Province. The data used are secondary data obtained from the publication of the Department of Industry and Trade of South Sumatera Province. The analytical method used is a quantitative analysis of panel data regression analysis equipment. The results showed that investment significantly positive effect on employment in the formal small industries in the district/ city of South Sumatera Province. Keywords: Investment; Employment; Formal Small Industry JEL Classification: L00